ANXIETY OF CHILDREN WHO HAVE MENTAL RETARDATION AT BINA PUTRA SPECIAL SCHOOL - Desi, Desi; Dary, Dary; Virgia, Ollyvia Vena (Jurnal Keperawatan Respati Yogyakarta, 2020)
Anxiety is a psychological problem that has many types and can affect everyone from children to teenagers and parents. Prolonged anxiety will cause interference that will affect growth and development, both in normal children and children with special needs such as mental retardation. Mental retardation is someone who has limited intellectual functioning, intelligence functions, limitations in socializing and limited adaptive abilities that cause disrupting effects of the process of cognitive, psychomotor development and experience immature emotions which results in children being irritable, depressed, unable to hold back and experiencing anxiety excessive. The aim of this study was to obtain data related to the percentage of anxiety symptoms in girls and boys with mental retardation. This study uses a quantitative method with a descriptive approach and respondents in this study are students who experience mental retardation at the Bina Putra Special School. Data collection techniques used a measuring device based on the Glasgow Anxiety Scale by Midham J. and Espie, C. which has been adapted into Indonesian. The results of this study showed that 19 male students with mental retardation were identified 14 students had anxiety disorders and 18 female students with mental retardation were identified 16 students had anxiety disorders. This can be caused by several factors, including: problems in the family, the school environment, both stressors from school activities, teachers and schoolmates.